Visualization and Quantification of Genetically Adapted Microbial Cells During Preculture - Kim, Hyun Ju; Jeong, Haeyoung; Lee, Sang Jun (Frontiers in Microbiology, 2021)
As culture history is known to affect the length of the lag phase and microbial cell growth, pre-cultures are often grown in the same medium as the main culture for physiological adaptation and to reduce a prolonged lag time in some microbial cells. To understand the adaptation process of microbial cells during transfer from LB medium to minimal medium, we used the growth of E. coli BL21(DE3) in succinate minimal medium as a model system. We observed that only one or two sequential transfers from minimal medium to fresh minimal medium accelerated the growth rate of BL21(DE3) cells. In addition, the number of large colonies ( diameter 0.1 cm) on succinate agar increased with the number of transfers. Genome and transcript analyses showed that the C to T point mutation in large colony cells converted the inactive promoter of kgtP (known to encode -ketoglutarate permease) to the active form, allowing efficient uptake of exogenous succinate. Moreover, we visualized the occurrence of genetically adapted cells with better fitness in real-time and quantified the number of those cells in the microbial population during transfer to the same medium. Fluorescence microscopy showed the occurrence and increase of adapted mutant cells, which contain intracellular KgtP-fused green fluorescent proteins, as a result of the C to T mutation in the promoter of a fused kgtP–sfgfp during transfer to fresh medium. Flow cytometry revealed that the proportion of mutant cells increased from 1.75% (first transfer) to 12.16% (second transfer) and finally 70.79% (third transfer), explaining the shortened lag time and accelerated growth rate of BL21(DE3) cells during adaptation to the minimal medium. This study provides new insights into the genetic heterogeneity of microbial populations that aids microbial adaptability in new environments.